2017
DOI: 10.7150/thno.20586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation and First In-Human Use of [44Sc]Sc-PSMA-617 for PET Imaging of Metastasized Castrate-Resistant Prostate Cancer

Abstract: Background: Various trivalent radiometals are well suited for labeling of DOTA-conjugated variants of Glu-ureido-based prostate-specific membrane antigen (PSMA) inhibitors. The DOTA-conjugate PSMA-617 has proven high potential in PSMA radioligand therapy (PSMA-RLT) of prostate cancer as well as PET imaging when labeled with lutetium-177 and gallium-68 respectively. Considering the relatively short physical half-life of gallium-68 this positron emitter precludes prolonged acquisition periods, as required for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 29 publications
3
114
1
5
Order By: Relevance
“…An in vitro binding study of [ 212 Pb]Pb‐NG001 and [ 212 Pb]Pb‐PSMA‐617 to C4‐2 cells yielded k d values of 22.0 and 11.1 nM, respectively (Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA‐positive cells . Gourni et al showed that [ 11 In]In‐PSMA‐617 to LNCaP cells yielded a k d of 5.4 nM .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An in vitro binding study of [ 212 Pb]Pb‐NG001 and [ 212 Pb]Pb‐PSMA‐617 to C4‐2 cells yielded k d values of 22.0 and 11.1 nM, respectively (Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA‐positive cells . Gourni et al showed that [ 11 In]In‐PSMA‐617 to LNCaP cells yielded a k d of 5.4 nM .…”
Section: Discussionmentioning
confidence: 96%
“…42,43 Figure S4), which are in agreement with other studies that have examined the binding of PSMA ligands to PSMA-positive cells. [44][45][46] Gourni et al showed that [ 11 In]In-PSMA-617 to LNCaP cells yielded a k d of 5.4 nM. 44 Umbricht et al reported that [ 177 Lu]Lu-PSMA-617, [ 44 Sc]Sc-PSMA-617 and [ 68 Ga] Ga-PSMA-617 to PC-3 PIP cells gave the k d values of 39, 33 and 72 nM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Eppard et al investigated in a first in human study the PET tracer 44 Sc‐PSMA‐617 in patients with progressive, multiple metastases of PCa. They demonstrated the feasibility of imaging PCa tissue with an excellent image quality even 18 hours post injection allowing therapeutic dosimetric assessment prior to 177 Lu‐PSMA therapy as recently shown by Khawar et al…”
Section: Introductionmentioning
confidence: 82%
“…44 Sc obtained in this manner was labelled to DOTATOC and, subsequently, applied to a patient for the first time . More recently, generator‐produced 44 Sc was used to prepare 44 Sc‐PSMA‐617 and injected into prostate cancer patients …”
Section: Radiometals For Theranostic Applicationsmentioning
confidence: 99%
“…79 More recently, generator-produced 44 Sc was used to prepare 44 Sc-PSMA-617 and injected into prostate cancer patients. 84 As an alternative, the production of 44 Sc was proposed using natural calcium at a cyclotron using the nat Ca(p, n) 44 Sc nuclear reaction. 85 While acceptable yields of 44 Sc were obtained after 1-hour irradiation with protons, radioisotopic impurities such as 44m Sc (T 1/2 = 58.6 h), 47 Sc (T 1/2 = 3.35 d), and 48 Sc (T 1/2 = 43.7 h) were also present in the final product.…”
Section: /44/47 Scmentioning
confidence: 99%